Cold stress promotes IL-33 expression in intestinal epithelial cells to facilitate food allergy development. (December 2020) - Liu, Jiang-Qi; Hu, Tian-Yong; Diao, Kai-Yuan; Yu, Dian; Song, Yan-Nan; Mo, Li-Hua; Yang, Gui; Liu, Zhi-Qiang; Liu, Zhi-Gang; Yang, Ping-Chang
Abstract: Background: The causative factors and pathogenesis of food allergy (FA) is not fully understood yet. Cold stress (CS) occurs frequently in human life that influences physiological activities in the body. In this study, we aimed to investigate the chronic CS (CS) effects on promoting the expression of IL-33 in intestinal epithelial cells. Methods: CS was carried out by placing mice at 4 °C for 1 h daily for 7 consecutive days. We developed a mouse model used to test the effects of CS on the FA development. Results: We found that, similar to conventional FA mouse model, CS induced the core body temperature to drop markedly in mice, increased intestinal epithelial barrier permeability and facilitated FA development. CS promoted interleukin (IL)-33 expression in intestinal epithelial cells through the adrenocorticotropic hormone (ACTH)/cortisol axis and via inducing the Il33 promoter methylation. CS facilitated the FA development in mice, that could be blocked by depletion of IL-33 expression in intestinal epithelial cells. Conclusions: CS induces IL-33 expression in intestinal epithelial cells to promote Th2 polarization in the intestinal tissues and facilitates FA development.